Pengaruh Influencer Media Sosial dan Konten Media Sosial terhadap Keputusan Pembelian Produk Skintific di Kota Malang - Qonitatur Sofia Azzakiyah Sofia; Lina Buadiarti; Baroroh Lestari (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. Social media has become an important space for consumers to search for, compare, and assessinformation before purchasing skincare products. This shift means that promotional effectiveness is nolonger determined only by the popularity of the figure delivering the message, but also by the quality ofinformation received by consumers. This study analyzes the influence of social media influencers and socialmedia content on purchase decisions for Skintific products in Malang City, both partially andsimultaneously. The study employed a quantitative approach with a causal associative design. Data werecollected through an online questionnaire from 100 Skintific consumers selected using purposive sampling.Respondents lived in Malang City, were aged 17 to 45 years, actively used social media, followed TasyaFarasya, and had purchased Skintific products between November 2023 and January 2024. Data wereanalyzed using SPSS version 25 through classical assumption tests, multiple linear regression, partial tests,simultaneous tests, and the coefficient of determination. The results show that social media influencershave a positive and significant effect on purchase decisions, with a regression coefficient of 0.477 and asignificance value of 0.001. Social media content also has a positive and significant effect, with a regressioncoefficient of 0.489 and a significance value below 0.001. Simultaneously, both variables significantlyaffect purchase decisions, with an F value of 145.858. The Adjusted R Square value of 0.650 indicates thatthe model explains 65 percent of the variation in purchase decisions. Social media content has a relativelystronger contribution than social media influencers. These findings suggest that Skintific should combinecredible influencers with engaging, accurate, accessible, and relevant content so that promotion does notstop at initial attention but supports more considered purchase decisions.Keywords: digital marketing, purchase decision, Skintific, social media content, social media influencer